1998
DOI: 10.1046/j.1523-1747.1998.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effects of Heat on Normal Human Melanocyte Growth and Melanogenesis: Comparative Study with UVB

Abstract: Although energy-rich ultraviolet B (UVB) is considered to be primarily responsible for most of the effects associated with solar radiation, small energy recorded as heat appears to contribute to the biologic effects of solar radiation on the skin. We compared the effects of heat and UVB on normal human melanocyte functions. In monolayer culture the following was found. (i) Heat-treated melanocytes showed an increased dendricity and exhibited a larger cell body compared with nontreated melanocytes. (ii) After m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 55 publications
(54 reference statements)
3
26
0
1
Order By: Relevance
“…Their results have also shown that the tyrosinase activity in human melanocytes increased slightly after UVB and heat treatments, by 2.0% and 5.0%, respectively. The authors suggest that heat may share significant biologic activities with UVB in melanocyte functions and conclude that these reactions could be considered as one of the protective or adaptive responses of the skin pigmentary system to the environment (Nakazawa et al, 1998). Our earlier studies have also shown the down-regulation in melanogenesis when the cells were exposed to increasing concentrations of the tested substances (Beberok et al, 2013;Wrześniok et al, 2013a,b).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Their results have also shown that the tyrosinase activity in human melanocytes increased slightly after UVB and heat treatments, by 2.0% and 5.0%, respectively. The authors suggest that heat may share significant biologic activities with UVB in melanocyte functions and conclude that these reactions could be considered as one of the protective or adaptive responses of the skin pigmentary system to the environment (Nakazawa et al, 1998). Our earlier studies have also shown the down-regulation in melanogenesis when the cells were exposed to increasing concentrations of the tested substances (Beberok et al, 2013;Wrześniok et al, 2013a,b).…”
Section: Discussionmentioning
confidence: 86%
“…The small increase of melanogenesis was also stated by other authors. Nakazawa et al (1998) reported the regulatory effects of heat on normal human melanocytes functions, such as the inhibition of melanocyte growth, the upregulation of p21 and p53 expressions, and the stimulation of melanogenesis by increasing the number of DOPA-and TRP1-positive melanocytes in coculture with keratinocytes. Their results have also shown that the tyrosinase activity in human melanocytes increased slightly after UVB and heat treatments, by 2.0% and 5.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Diosgenin has been shown to exert anti-proliferative and proapoptotic actions on rheumatoid arthritis synoviocytes or on cancer cells in vitro Briganti et al, 2003;Oka et al, 1996) and in vivo , as well as differentiating effects (Nakazawa et al, 1998). However, the effect of diosgenin on pigmentation has not yet been elucidated.…”
Section: Diosgenin Inhibits Melanogenesis In B16 Melanoma Cellsmentioning
confidence: 99%
“…This compound has been reported to have various biological effects in vivo (Cullen, 1998;Ortonne and Nordlund, 1998). Moreover, at an appropriate dose, diosgenin has been shown to exert anti-proliferative and proapoptotic actions on rheumatoid arthritis synoviocytes (Liagre et al, 2004) or on cancer cells in vitro Briganti et al, 2003;Oka et al, 1996) and in vivo , and also exerts differentiating effects (Nakazawa et al, 1998). It is also the starting material for the synthesis of a number of hormonal products such as dehydroepiandrosterone (Scott et al, 2001) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Data indicate that UVB can influence the expression of TRP-1 [60,61]. Repeated UVB irradiation induced TRP-1 expression in melanocyte-keratinocyte co-culture [62]. In our experiments, direct UVB exposure caused a decrease in TRP-1 mRNA expression in melanocytes.…”
Section: Discussionsupporting
confidence: 57%